Combine like terms to simplify an expression. For example, all terms with the variable x can be combined into one term. All constants can also be combined.
1) -4x - 10x = -14x
2) -r - 10r = -11r
3) -2x + 11 +6x = 4x + 11
4) 11r - 12r = -r
5) -v + 12v = 11v
6) -8x - 11x = -19x
7) 4p + 2p = 6p
8) 5n + 11n = 16n
9) n + 4 - 9 - 5n = -4n - 5
10) 12r + 5 + 3r - 5 = 15r (the 5 and -5 cancel each other out)
11) -5 + 9n + 6 = 9n + 1
I think it is either 4.41 or 1.84 Sq Ft
<span>The correct solution to this mathematical problem is AB2=BC2+AC2 or AB is a square root from the addition of the exponential values from both BC and AC. The final result is AB= 2.91547594742. It is easy to get the result by calculating the square root from the addition of the exponentiations of the values from the two sides of the triangle that we already have. We already have the value from BC=2,7 and AC=1,1, the angle C is 90 degrees. The equation comes from the old Pitagoras theorem which says that in a right triangle or triangle in which one of the angles is 90 degrees the exponential value of the hypotenuse is equal to the addition of the exponential values from the other two sides of this triangle. As for the other angles of this triangle, angle A and angle B we can find their values using this equation sinA=BC/AB and sinB=AC/AB or angle which are also applicable for right triangles. The function sin is a proportion from the opposite side of a right angle in the triangle and the hypotenuse of the same triangle. According to these equations the value of angle A is 67 degrees and angle B is 23 degrees. To verify the result from this equation we can use the rule that says the result from the addition of the three angles from each triangle should always be 180 degrees. In this case angle A + angle B + angle C = 67+23+90 = 180, which means that we got the right answer.</span>
The answer would be 5/2q+9r+6r-20s
Explanation
We have the equation
5(1/2q+3r-4s)
which would equal
5/2q+15r-20s
so with the information
We can subtract 6r from 15r to get 9r
15r-6r=9r
+9r would be the missing piece
So we substitute it in to make the equation true.
5/2q(+9r)+6r-20s
Hope this helps or was correct
i am pretty sure the answer is 9